Coumarin‐Chalcones Generated from 3‐Acetylcoumarin as a Promising Agent: Synthesis and Pharmacological Properties. Issue 11 (17th March 2022) - Nasab, Narges Hosseini; Azimian, Fereshteh; Kruger, Hendrik G.; Kim, Song Ja
Abstract: Developing novel chemical entities via different reactions and mechanisms is one of the hottest topics in drug development. The coumarin moiety displays good cell permeability and has numerous medicinal and pharmaceutical applications. It is utilized in the preparation of a wide range of molecules. Herein, we have focused on the application of 3‐acetylcoumarin as a starting material for the systematic synthesis of various types of heterocyclic compositions including coumarin‐chalcone compounds, which exhibit a broad variety of bioactivities, including antituberculosis; enzyme‐inhibition; antioxidant; anti‐inflammatory etc. After introducing the synthesis of 3‐acetylcoumarin, the review proceeds with a comprehensive presentation of the synthesis of coumarin‐chalcones under various conditions. Last, the reactions of prepared coumarin‐chalcones through different mechanisms and the outcomes achieved through such reactions are discussed. It is envisaged that this review will prompt researchers to expand on the knowledge gained in this field the last twenty years. Abstract : Coumarins (2 H ‐1‐benzopyran‐2‐one) with a wide range of biological and therapeutic activities have gained a reputation for developing various types of heterocyclic compounds. Coumarin analogues like 3‐acetylcoumarin can react with a variety of precursors containing aldehyde functional groups to produce coumarin‐chalcone compounds under different conditions. Through coumarin‐chalcones as a starting material, a wide range of compounds with biological properties such as antituberculosis, antioxidant, anti‐inflammatory and anticancer are produced using Krohnke and cycloaddition mechanisms.